Comparison of ground reaction force and contact time during various-direction lunges between badminton shoes without and with a lateral forefoot wedge sole - Chen, W.-H.; Chen, C.-H.; Yang, W.-W.; Lin, G.-Y.; Hsu, W.-C.; Shiang, T.-Y.; Liu, C. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
This study compared the ground reaction force (GRF), GRF ratio, and contact time between badminton shoes without and with a lateral forefoot wedge sole during lunges in three directions. Fifteen collegiate athletes wore forefoot wedge shoes (5° incline) and control shoes without a lateral forefoot wedge sole (in random order) and performed three typical badminton lunge movements (forward, lateral, and backward directions). A total of nine GRF, GRF ratio, and contact time parameters were analyzed. A paired t test was performed to assess the differences between two shoes. The significance level was set at p < 0.0056 (0.05/9) based on Bonferroni correction to avoid chances of type 1 errors. In the forward lunge, the forefoot wedge shoes resulted in a significantly higher average vertical ground reaction force (GRFv, 3.9%), average horizontal GRF (GRFh, 7.8%) in the braking phase and higher average GRFh (3.9%) in the propulsion phase than the control shoes. In the lateral lunge, the forefoot wedge shoes resulted in a significantly shorter total contact time (-4.6%) than the control shoes in the backward lunge, the forefoot wedge shoes resulted in a significantly higher GRFh to GRFv ratio (6.4%) in the braking phase compared with the control shoes. Thus, shoes with a lateral forefoot wedge sole can effectively enhance mechanical performance in direction changes during forward and backward badminton lunges, and shorter the contact time during lateral badminton lunges. Shoes with a lateral forefoot wedge sole can be considered when designing athletic footwear.